Analisis Pengawasan Ketenagakerjaan Jasa Konstruksi Terhadap Keselamatan Jasa Konstruksi (Studi Kasus pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Kalimantan Utara) - Masir, Masir; Abidin, Zainal (Borneo Engineering : Jurnal Teknik Sipil, 2018)
The existence of a tendency of violations that are often done by contractors requires an effort to increase labor inspection. With the existence of an appropriate pattern of labor inspection by government employee of labor inspector in construction service sector then every execution of a work can be executed according to rule so that it can run well and according to what we expected. The objectives of this research was to know the effect of labor inspection to the safety of construction services in the Office of Manpower and Transmigration of North Kalimantan Province. Data collection technique used was questionnaires. The data collected in this research consisted of primary and secondary data, This resesearch was done through questionnaire technique. The samples in this study were 20 respondents from Office of Manpower and Transmigration of North Kalimantan Province in the field of labor inspection. Data obtained was scored into Likert method and then analyzed by SPSS program. The results showed that there was a positive relationship between Labor Inspection with Work Safety, which can be explained in the form of linear regression equation i.e.: Y = 32.128 + 0.250 X, with the coefficient of determination (R 2 ) was 0.173 and coefisient of correlation (r)was 0.42.